Partial Gastrectomy for Peptic Ulcer. Issue 2 (June 1960) - Brookes, Victor S.; Waterhouse, J. A. H.; Thorn, P. A.
Abstract : This paper reports a study of 955 patients in whom partial gastrectomy was performed for peptic ulcer. An analysis is presented of the clinical and operative factors which may influence the success of the operation.